Push-out bond strength of different intracanal posts in the anterior primary teeth according to root canal filling materials - Nilgoon Pasdar; Bahman Seraj; Mostafa Fatemi; Shirin Taravati (Wolters Kluwer Medknow Publications, 2017)
Background: This study was carried out to evaluate the effect of root canal filling on the bond strength of three intracanal posts in the primary incisors. Materials and Methods: Sixty primary incisors were prepared and then divided into two groups (n = 30). The first group canals obturated with zinc oxide eugenol (ZOE) and Group 2 canals obturated with Metapex. Further, the two group categories were divided into three subgroups (n = 10): (1) short composite post (SCP), (2) glass fiber posts (GFPs) cemented with flowable composite, and (3) GFP with glass ionomer cement (GFP + GIC). The push-out test was performed with a universal testing machine. The results were statistically analyzed with two-way analysis of variance.(α = 0.05). Results: The mean bond strength of the first group obturated with ZOE was lower than that of the second group obturated with Metapex (P = 0.046). Moreover, from a statistical point of view, in all three subgroups, the correlation of mean push-out bond strength between SCP and GFP coated with flowable composite was not substantial at P = 0.97. However, the mean bond strength of SCP was in fact significantly greater than that of the GFP coated with GIC since P = 0.034. Conclusion: Using ZOE resulted in the significant reduction of the mean bond strength of the intracanal posts when utilized in the primary anterior teeth. Likewise, SCP and GFP coated with flowable composite showed higher push-out bond strengths for restoring primary anterior teeth.